Phytochemical Evaluation, Antioxidant and Antimicrobial Activities of Various Extracts from Leaves and Stems of Bryophyllum pinnatum - Daniel, Imaobong E.; Akpan, Ekemini I.; Utam, Edidiong C. (Nepal Journal of Biotechnology, 2020)
Antioxidant and antimicrobial activities of different extracts (methanol and ethyl acetate) of leaf and stem of Bryophyllum pinnatum were studied. The screening for the secondary metabolites was carried out using the standard methods. The antioxidant capacities of the different extracts were assessed using DPPH (2,2-diphenyl-1-picrylhydrazyl) radicals and Ferric reducing antioxidant power (FRAP) while the antimicrobial activity of the extracts obtained were screened against Gram-positive, Gram-negative bacteria and fungi (Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa Salmonella spp., Vibrio cholerae, Candida albicans and Aspergillus niger) using Agar well diffusion method. Both extracts obtained from leaf and stem of Bryophyllum pinnatum contained most of the phytochemical compounds tested for. However, anthocyanins and anthraquinone were not detected in leaf extracts while coumarin was absent in stem extracts. Quantification of bioactive compounds showed that both extracts contained the highest concentration of polyphenols (34.49 ±0.47 mg GAE/g and 32.32 ±1.2 mg GAE/g for methanol leaf and stem extracts respectively) while the least concentration was recorded for alkaloids (0.03±0.02 mg/g for methanol stem extract). Results revealed that the extracts showed dose-dependent scavenging of DPPH as well as the ability of the extracts to reduce FeCl3 solution, with methanol extracts exhibiting the highest scavenging and reducing capacity. However the leaves of Bryophyllum pinnatum had greater antioxidant activity than the stem by DPPH and ferric reducing assays, with IC50 values ranging from 3.147µg/ml to 3.80µg/ml for DPPH and 331.9 - 451 µg/ml for FRAP assays. The antimicrobial activity of various solvent extracts of leaf and stem reveal that microorganisms exhibited different sensitivities towards these extracts in a dose-dependent manner. Methanol leaf extract showed no activity against Escherichia coli while Pseudomonas aeruginosa was insensitive to ethyl acetate leaf extract. For stem extracts, Aspergillus niger, Vibrio cholerae and Pseudomonas aeruginosa were resistant to methanol extract while Aspergillus niger, Salmonella spp. and Pseudomonas aeruginosa was resistant towards ethyl acetate stem extract. The results obtained in this study showed that Bryophyllum pinnatum is a reservoir of bioactive compounds and both extracts exhibited significant antimicrobial and antioxidant activity.